Southern fried sass : a queen's guide to cooking, decorating, and living just a little "extra" - Minj, Ginger, 1984-; Glatzer, Jenna (Atria Books, 2023)
"In this tongue-in-cheek memoir-cum-life manual-cum-cookbook, complete with all of Ginger's Southern-inspired favorite recipes, fans will learn about some of Ginger's most vulnerable and celebratory moments. Each chapter will be organized around a theme or lesson from Ginger's life, from her grandmother's brand of Southern resilience to fighting for what you're worth, how a big girl can look good on a motorcycle, finding love, and making damn good cupcakes"--